The effect of home-based transcranial direct current stimulation in cognitive performance in fibromyalgia: A randomized, double-blind sham-controlled trial - Serrano, Paul Vicuña; Zortea, Maxciel; Alves, Rael Lopes; Beltrán, Gerardo; Bavaresco, Cibely; Ramalho, Leticia; Alves, Camila Fernanda da Silveira; Medeiros, Liciane; Sanches, Paulo R. S.; Silva, Danton P.; Lucena da Silva Torres, Iraci; Fregni, Felipe; et al. (Frontiers in Human Neuroscience, 2022)
Background Transcranial Direct Current Stimulation (tDCS) is a promising approach to improving fibromyalgia (FM) symptoms, including cognitive impairment. So, we evaluated the efficacy and safety of home-based tDCS in treating cognitive impairment. Besides, we explored if the severity of dysfunction of the Descendant Pain Modulation System (DPMS) predicts the tDCS effect and if its effect is linked to changes in neuroplasticity as measured by the brain-derived neurotrophic factor (BDNF). Methods This randomized, double-blind, parallel, sham-controlled clinical trial, single-center, included 36 women with FM, aged from 30 to 65 years old, assigned 2:1 to receive a-tDCS (n = 24) and s-tDCS (n = 12). The primary outcome was the Trail Making Test’s assessment of executive attention, divided attention, working memory (WM), and cognitive flexibility (TMT-B-A). The secondary outcomes were the Controlled Oral Word Association Test (COWAT), the WM by Digits subtest from the Wechsler Adult Intelligence Scale (WAIS-III), and quality of life. Twenty-minute daily sessions of home-based tDCS for 4 weeks (total of 20 sessions), 2 mA anodal-left (F3) and cathodal-right (F4) prefrontal stimulation with 35 cm2 carbon electrodes. Results GLM showed a main effect for treatment in the TMT-B-A [Wald χ2 = 6.176; Df = 1; P = 0.03]. The a-tDCS improved cognitive performance. The effect size estimated by Cohen’s d at treatment end in the TMT-B-A scores was large [–1.48, confidence interval (CI) 95% = –2.07 to–0.90]. Likewise, the a-tDCS effects compared to s-tDCS improved performance in the WM, verbal and phonemic fluency, and quality-of-life scale. The impact of a-tDCS on the cognitive tests was positively correlated with the reduction in serum BDNF from baseline to treatment end. Besides, the decrease in the serum BDNF was positively associated with improving the quality of life due to FM symptoms. Conclusion These findings revealed that daily treatment with a home-based tDCS device over l-DLPFC compared to sham stimulation over 4 weeks improved the cognitive impairment in FM. The a-tDCS at home was well-tolerated, underlining its potential as an alternative treatment for cognitive dysfunction. Besides, the a-tDCS effect is related to the severity of DPMS dysfunction and changes in neuroplasticity state. Clinical trial registration [www.ClinicalTrials.gov], identifier [NCT03843203].